'A happy coincidence': race, the cold war, and Frank M. Snowden, Jr's Blacks in Antiquity. (24th February 2021) - Parmenter, Christopher Stedman
Abstract: Between 1947 and 2001, the African American professor, diplomat, and dean Frank M. Snowden, Jr laid out an influential thesis about 'race relations' in the ancient Mediterranean. According to Snowden, Greeks and Romans were 'white'; Africans, whom Greeks and Romans called 'Ethiopians', were 'black'; Greek and Roman societies lacked modern 'color prejudice'. In this article, I contextualize the development of Snowden's 'race relations' thesis in the politics of the early Cold War. Reviewing Snowden's research notes archived at Howard University, I argue that Snowden — who travelled widely after the Second World War as a US diplomat — purposefully distanced his thesis from the sociology of race during the 1940–50s. Instead, Snowden envisioned American racial categories as permanent fixtures of world history, optimistically looking to Greece and Rome as models for a post-segregation America. Finally, I trace the enduring impact of Snowden's thesis by unpacking his historiography of Naukratis in the Archaic Period, which he had identified as the west's first multiracial society.